A REVIEW OF PHYTOCHEMICAL PROPERTIES, ANTIBACTERIAL ACTIVITY, AND TOXICITY STUDY OF Averrhoa bilimbi LEAVES AND FRUIT - Leliqia, Ni Putu Eka; Safitri, Intan (Journal Pharmaceutical Science and Application; Vol 3 No 1 (2021): Journal Pharmaceutical Science and ApplicationDO - 10.24843/JPSA.2021.v03.i01.p04, 2021)
Background: Averrhoa bilimbi or starfruit is a plant that is commonly found in Indonesia. A. bilimbi is widely used as herbal therapy against various diseases, especially those caused by bacteria. Objective: This article is intended to provide information regarding the chemical content of A. bilimbi, its antibacterial potential, and its safety level. Methods: The preparation of this article used a systematic literature review method of articles that have been published in both national and international scientific journal. Result: Leave and fruit of A. bilimbi is known to contain several classes of primary and secondary metabolites, namely carbohydrates, proteins, fats, flavonoids, alkaloids, glycosides, saponins, tannins, triterpenoids, and steroids. A. bilimbi also contains several macros and micro minerals including calcium (Ca), magnesium (Mg), and zinc (Zn). A. bilimbi could inhibit the growth of various Gram-positive and negative bacteria which have been proven through in vitro testing with diffusion and dilution methods. Based on the acute toxicity study, it was found that 80% ethanol extract of A. bilimbi fruit had an LD50 value of above 5.000 mg/kg BW so that it is practically non-toxic. Based on sub-chronic toxicity of A. bilimbi up to a dose of 500 mg/kg BW there was no death in the test animals and shows a toxic effect. Conclusion: The leaves and fruit of A. bilimbi have antibacterial activities. The compounds contained in A. bilimbi are thought to have a role in its antibacterial activity. Based on several toxicity studies, the ethanol extract of A. bilimbi has been proven safe to use. Keywords: Averrhoa bilimbi, Starfruit, Antibacterial, Chemical Properties, Toxicity.